ÉVALUER UNE INTERVENTION COMPLEXE: ENJEUX CONCEPTUELS, MÉTHODOLOGIQUES, ET OPÉRATIONNELS - Contandriopoulos, André-Pierre (Can J Program Eval, 2011)
Theoretically, evaluation should help decision-makers address contemporary health system challenges. Paradoxically, the use of evaluation results by decision-makers remains poor, despite rapid development in the evaluation field. The level of use depends on the evaluator’s ability to account for the complexity of health-care systems. The complex nature of an intervention often compels evaluators to adopt unconventional approaches to account for the roles of the players. The evaluation of a complex intervention raises conceptual, methodological, and operational challenges the evaluation has to overcome to increase the level of use of its findings by decision-makers.